2020
DOI: 10.14712/18059694.2020.11
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of the Impact of Gadolinium Orthovanadate GdVO4:Eu3+ Nanoparticles on the Carrageenan-Induced Intestinal Inflammation

Abstract: Aim: To evaluate the effects of orally administered gadolinium orthovanadate GdVO4:Eu3+ nanoparticles (VNPs) on the course of chronic carrageenan-induced intestinal inflammation. Methods: Samples of small intestinal tissue were collected from four groups of rats (intact, after administration of VNPs, with carrageenaninduced intestinal inflammation, with carrageenan-induced intestinal inflammation orally exposed to VNPs) to assess the intestinal morphology and HSP90α expression. Levels of seromucoid, C-reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Балл от 0 до 5 присваивался при наличии, соответственно, 0-2, 3-5, 6-8, 9-11, 12-14, 15 и более окрашенных клеток. В каждом микропрепарате оценивали 5 полей зрения [11].…”
Section: материалы и методыunclassified
“…Балл от 0 до 5 присваивался при наличии, соответственно, 0-2, 3-5, 6-8, 9-11, 12-14, 15 и более окрашенных клеток. В каждом микропрепарате оценивали 5 полей зрения [11].…”
Section: материалы и методыunclassified
“…Some authors demonstrated that the low molecular weight carrageenan significantly reduces blood serum levels of TC, TG and LDL-C and improves the concentration of HDL-C in HFD fed mice, with a much stronger activity than that of high molecular weight carrageenan [50]. Furthermore, a considerable number of studies have shown that carrageenan causes inflammation [51][52][53], which should be fully considered in further studies, as this puts forward some limitations on the risk-free application of carrageenan. Although with certain side effects, further in-depth research on molecular mechanisms will help the development and utilization of Carrageenan.…”
Section: Carrageenanmentioning
confidence: 99%